'Nineteenth‐Century' Subdominants. (2nd September 2022) - SCHMALFELDT, JANET
ABSTRACT: The harmonic dualist notion of two commensurate 'systems' – authentic and plagal – proposed by Daniel Harrison in 1994 has not been widely accepted, but it enabled him to uncover strong plagal elements in the music of late nineteenth‐century European composers, and it gives much heft to the generally accepted view that the subdominant acquired greater autonomy in music of the fin de siècle. If we allow for the idea that the subdominant and the dominant play dual, though emphatically unequal, roles in tonal music, then it might follow that the subdominant in ascendency suggests the dominant in decline. Are there signs within Austro‐German music of the earlier nineteenth century that the subdominant had begun to assume this more ascendant status? I answer in the affirmative, with examples from the music of Ludwig van Beethoven, Franz Schubert, Fanny Hensel, Robert Schumann, Felix Mendelssohn, Richard Wagner and the young Johannes Brahms. Instances of the affective character of the subdominant in this music run the gamut from associations with the pastoral, with the world of night and dreams and magic, to implications of the ecstatic and, finally, to the expression of deepest grief.